Az internet szerepe a magyar mint idegen nyelv oktatásban. - Németh, Szabolcs (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2011)
Internet-based language teaching and e-learning are very popular topics nowadays. Many studies have been published on the subject, especially related to ESL. This article aims at describing internet-based resource materials that can be used in language class for learning and teaching Hungarian as a Second Language. It will present two websites specifically designed for learning Hungarian and different e-learning projects in order to discuss the basic differences between text-based and network-based language teaching/learning and the difference of methods applied in different projects.
The Role of the Internet in Teaching Hungarian as a Second Language
Keywords: E-learning; Teaching Hungarian as a Second Language; ESL; Learning Hungarian